Perikoncepcijska suplementacija folnom kiselinom: znanja, stavovi i savetodavna praksa farmaceuta i farmaceutskih tehničara u Srbiji - Zeković, Milica T; Krajnović, Dušanka; Nikolić, Marina; Stojković, Tatjana; Gurinović, Mirjana; Glibetić, Marija (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The protective effect of periconceptional folic acid supplementation in reducing the risk of neural tube defects (NTDs) and other adverse pregnancy outcomes has been scientifically confirmed. The present study aimed to assess knowledge, attitudes, and practice (KAP) of community pharmacists and pharmacy technicians with regards to counselling women of reproductive age on adequate folate intake. Methods. The cross-sectional study was conducted among the nationwide stratified sample of pharmacists and pharmacy technicians, practicing in both private and state-owned community pharmacies in Serbia. The detailed literature review, expert consultation and pre-testing were employed in the questionnaire development. The descriptive and inferential statistical analyses were performed using the SPSS software ver. 22. Results. Among 730 survey participants, 96.6% correctly identified types of deformities that could be prevented by folic acid and 77.0% recognized recommended dosage for women capable of becoming pregnant. However, fewer were able to recognize the optimal timing for folic acid supplementation (61.1%) and the proper dose for the NTD recurrence prevention (42.9 %). While 43.2% of pharmacy technicians thought that it was not their responsibility to provide a counselling concerning the measures for the prevention of congenital anomalies, only 4.7% of licensed pharmacists and none of the interns were of that opinion (χ2 = 198.287; df = 4; p < 0.001). The majority of respondents (54.7%) reported provision of informative consultation concerning folic acid once a week, or few times a month, while only 10 stated to do so on a daily basis. In addition, based on self-report, only 36.7% of participants communicates information and advice regarding adequate folate status at their own initiative, while the rest addresses this topic only on the patients request, i.e., reactively. Conclusion. Although participants acknowledged the importance of their role in preconception health promotion, our findings revealed certain knowledge gaps as well as dominantly reactive counselling practice. Tailored educational interventions and professional support are needed to improve the engagement of community pharmacy personnel in this area of public health.